Tomato separation conveyor based on color and weight using microcontroller - Rahalia Dinda, Natasya; Tri Putra Yanto, Doni (Journal of Industrial Automation and Electrical Engineering, 2025)
Indonesia, as an agricultural country, has great potential in the agricultural sector, including horticultural commodities such as tomatoes. Post-harvest tomato processing, such as sorting by color and weight, is often done manually, leading to inefficiency and the potential for human error. This research aims to design and build a microcontroller-based tomato sorting conveyor to improve efficiency and product quality. This system utilizes a color sensor to identify the ripeness of tomatoes and a weight sensor to measure their weight. The microcontroller acts as the main controller, processing data from the sensors, making decisions, and regulating the conveyor mechanism to separate the tomatoes into the appropriate lanes. This research is expected to overcome the inefficiency problem in the manual tomato sorting process. With automatic separation by color and weight, the time and labor required are reduced, thereby reducing operational costs. Furthermore, the use of a microcontroller to process data precisely can help ensure that sorted tomatoes meet the desired quality standards. The results of this research are expected to contribute to the development of microcontroller-based technology in agriculture and serve as a reference for further research